Solve the following equation and check your result.

Q.2    5t – 3 = 3t – 5

Answers (1)

We have 

            5t - 3 = 3t - 5

Transposing 3t to the LHS and -3 to the RHS, we get:

           5t - 3t = -5 + 3

or            2t = -2

Dividing both sides by 2 :

             t = -1

Check:-             Put t = -1 in the LHS we have,

                             5t - 3 = 5(-1) - 3 = -5 -3 = -8

                         Similarly put t = -1 in the RHS:

                             3t - 5 = 3(-1) - 5 = -3 - 5 = -8

    Hence,       LHS = RHS    

Exams
Articles
Questions